Childcare workers' experiences of supporting exclusive breastfeeding in Kuala Muda District, Malaysia: a qualitative study. Issue 1 (December 2016) - Mohd Suan, Mohd Azri; Ayob, Azrina; Rodzali, Maheran
Abstract Background The role of childcare workers at registered nurseries in supporting exclusive breastfeeding practice is important, as many newborn babies are placed in nurseries during working hours. To increase exclusive breastfeeding rates among working mothers, understanding childcare workers' experiences and needs relating to supporting these mothers is crucial. This study aimed to explore childcare workers' experiences of supporting breastfeeding at registered nurseries. Methods We used a qualitative design to conduct in-depth, semi-structured interviews with ten childcare workers at seven registered nursery centres in Kuala Muda District, Malaysia. Attitudes towards exclusive breastfeeding practice, experiences of breastfeeding training and information, and experiences supporting exclusive breastfeeding at the nursery were explored. Participants were asked to suggest improvements for exclusive breastfeeding practice at their nursery. All interviews were audio recorded, transcribed verbatim, and translated before analysis. Results All participants demonstrated a positive attitude in supporting and promoting exclusive breastfeeding practice, mainly centred on the advantages of breastfeeding. Various supports have been found such as labelling bottled breastmilk, allowing the mother to come to the nursery during breaks, and providing reading materials. However, several issues emerged that include parents' choice on infant feeding practice, insufficient content on breastfeeding topics during training, and adherence to the (not recommended) practice of bottle feeding expressed breastmilk. Recommendations to enhance breastfeeding were also suggested by participants. Conclusion Childcare workers may serve as another potential resource for sustaining exclusive breastfeeding at registered nurseries.